Small physical cross-linker facilitates hyaluronan hydrogels - Erikci, Saliha; Mundinger, Patricia; Böhm, Heike (Molecules, 2020)
In this study, we demonstrate that small charged molecules (NH4+, GluA+, dHA+) can form physical cross-links between hyaluronan chains, facilitating polymerization reactions between synthetically introduced thiol groups (HA-DTPH). These hybrid hydrogels can be obtained under physiological conditions ideally suited for 3D cell culture systems. The type and concentration of a physical crosslinker can be adjusted to precisely tune mechanical properties as well as degradability of the desired hydrogel system. We analyze the influence of hydrogen bond formation, concentration and additional ionic interactions on the polymerization reaction of HA-DTPH hydrogels and characterize the resulting hydrogels in regard to mechanical and biocompatibility aspects.